Association between changes in body composition and progression of liver fibrosis in patients with type 2 diabetes mellitus - Lin, Yuxi; Liang, Zhixing; Liu, Xiaofang; Chong, Yutian (Frontiers in Nutrition, 2024)
Aim: The correlation between type 2 diabetes mellitus (T2DM) and the occurrence of liver fibrosis is well-established. However, the longitudinal association between body composition and liver fibrosis progression in patients with T2DM remains incompletely explored. Methods: Total of 390 patients with T2DM underwent body composition assessments, followed by a median duration of 2.13 years. The calculated parameters included body mass index (BMI), fat mass index (FMI), trunk fat mass index (TFMI), appendicular skeletal muscle mass index (ASMI), muscle/fat mass ratio (M/F) and appendicular skeletal muscle mass/trunk fat mass ratio (A/T). Liver fibrosis was evaluated through liver stiffness measurement (LSM). Patients were classified according to BMI and body composition, followed by a comprehensive investigation into the impact of body composition changes on liver fibrosis outcomes. Results: Among 72 patients with incident advanced liver fibrosis at readmission, ΔBMI, ΔFMI and ΔTFMI increased, while ΔM/F and ΔA/T decreased. Individuals who kept obese had a dramatically elevated hazard of incident advanced liver fibrosis compared to those who kept non-obese, with an adjusted odds ratio of 3.464. When TFMI heightened, the hazard of incident advanced liver fibrosis was 3.601 times higher compared to the decreased group. Additionally, individuals in increased ASMI and A/T groups showed a slight advantage in preventing incident advanced liver fibrosis compared to the stable groups. Conclusions: Stable obesity was associated with a greater hazard of liver fibrosis advancement, and an increase in TFMI may promote the progression of liver fibrosis. Maintaining a balanced muscle/fat ratio appeared to help prevent the progression.